Finding the Titanic - Ballard, Robert D.; Froman, Nan.; Marschall, Ken (New York : Scholastic, 1993)
Describes the voyage of the Titanic, the accident that caused it to sink, and the rescue of those who survived.
"Cartwheel books".
Grades 2 & 3.
Ages 7-9.
Keywords: Titanic (Steamship) -- Juvenile literature; Titanic (Steamship); Shipwrecks -- North Atlantic Ocean -- Juvenile literature; Underwater exploration -- North Atlantic Ocean -- Juvenile literature; Shipwrecks